Vitamin D deficiency in pregnancy and its effects on neonatal outcome - Gupta, Shweta; Jain, Kanupriya; Kaur, Jaspreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: India has one of the highest Vitamin D deficiency rates in pregnancy in the world and yet we have limited research to study its various effects from our country. We aim to study the prevalence of Vitamin D deficiency in pregnancy and effect on neonatal outcome after supplementation. Methods: 200 pregnant women were recruited at 26 weeks and more. They were divided into sufficient group (normal levels of the vitamin), supplemented group (recruited at 26 weeks and supplemented for 8 weeks) and unsupplemented group (recruited after 34 weeks and so could not be supplemented) based on time of recruitment and levels of vitamin D. They were followed up till discharge of newborn from the hospital. Neonatal outcomes were noted. Results: The prevalence of Vitamin D deficiency in pregnancy in present study was 94.5%. Vegetarians and urban residents were more likely to have this deficiency. Admissions to NICU were significantly less in neonates of vitamin D supplemented women. Conclusions: The prevalence of vitamin D deficiency is very high during pregnancy and further studies are needed to clearly define its role in neonatal outcome.